Tardive Dystonia: Clinical Spectrum and Novel Manifestations - R. Jeffrey Davis; Jeffrey L. Cummings; Robert W. Hierholzer (Behavioural Neurology)
Tardive dystonia was identified in 25 patients: involvement of the face and neck was most common; truncal and limb dystonia were also observed. There were 3 cases of laryngospasm and 2 of spasmodic dysphonia. The latter has not been previously reported as a manifestation of tardive dystonia. In all cases, movements typical of classic tardive dyskinesia could be demonstrated. This group illustrates the variety of dystonic disorders that may occur in conjunction with tardive dyskinesia.